Internal Crisis as a Security Challenge for a Nation State - Andrzej CZUPRYŃSKI (Communications of International Proceedings, 2020)
The occurrence of internal hazards in each country constitutes an integral part of the natural, biological, social and political conditions of each security entity. In the process of counteracting crisis threats, it is reasonable to take control of their symptoms and jurisdiction over their evolution in such a way as to minimize the negative effects, and thus prevent their escalation into a full-blown crisis. It is reasonable to assume that a calamity is characterized by: unpredictability as to the duration and path of the development of perils causing the crisis; the mass scale of dangers in a large area causing the crisis; long-term and continuous negative impact on the social, economic and cultural life of citizens; failure of public institutions aimed at securing the functioning of the society.
Keywords: Crisis; Crisis Management; Security.